Circulating tumour DNA for clinicians: current and future clinical applications. Issue 10 (October 2021) - Thompson, M.K.; Gale, D.; Brenton, J.D.
Abstract : This review introduces clinicians to the basic concepts of the biology of circulating tumour DNA (ctDNA), which is required to understand clinical use of ctDNA technology. We provide an overview of how new technology has improved the sensitivity of ctDNA detection over the last decade and the available techniques for ctDNA analysis including whole-genome sequencing (WGS), targeted cancer-associated gene panels, and methylation analysis. We discuss the most recent evidence from clinical trials for ctDNA in patient care including precision treatment of advanced cancers, disease monitoring, improving adjuvant treatment, and screening for early detection of cancer. Finally, we outline how ctDNA is likely to directly impact radiologists, and identify further research required for ctDNA to progress into routine clinical application.